2020
DOI: 10.1093/braincomms/fcaa027
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar lesions at a young age predict poorer long-term functional recovery

Abstract: Early studies on long-term functional recovery after motor and premotor lesions showed better outcomes in younger monkeys than in older monkeys. This finding led to the widespread belief that brain injuries cause less impairment in children than adults. However, this view has limitations and a large body of evidence now indicates that cerebral damages can be more harmful when inflicted at young age, during critical periods of neural development. To date, this issue has been mainly investigated in the context o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…Some studies reported that cerebellar damage at a young age contributed to more severe, and prolonged impairment in both cognitive and motor domains ( 41 , 42 ). However, multiple caveats in experimental design limited those studies ( 43 ). Beuriat et al, in a study of patients who were treated for a posterior fossa tumor, controlled all the major confounders (namely radiotherapy, tumor characteristics, damage to the deep cerebellar nuclei, and delay between surgery and assessment time) and reported that younger children had worse long-term performance compared to older children or adults in motor and cognitive tasks ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported that cerebellar damage at a young age contributed to more severe, and prolonged impairment in both cognitive and motor domains ( 41 , 42 ). However, multiple caveats in experimental design limited those studies ( 43 ). Beuriat et al, in a study of patients who were treated for a posterior fossa tumor, controlled all the major confounders (namely radiotherapy, tumor characteristics, damage to the deep cerebellar nuclei, and delay between surgery and assessment time) and reported that younger children had worse long-term performance compared to older children or adults in motor and cognitive tasks ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple caveats in experimental design limited those studies ( 43 ). Beuriat et al, in a study of patients who were treated for a posterior fossa tumor, controlled all the major confounders (namely radiotherapy, tumor characteristics, damage to the deep cerebellar nuclei, and delay between surgery and assessment time) and reported that younger children had worse long-term performance compared to older children or adults in motor and cognitive tasks ( 43 ). Since our participants suffered their injury at an adult age, it might also be a key factor that explains our lack of significant findings in our sub-group of cerebellar participants.…”
Section: Discussionmentioning
confidence: 99%
“…Only, Aarsen et al described a negative effect [ 1 ]. However, multiple caveats limited those studies [ 6 ]. Beuriat et al in a study of patients who were treated for a posterior fossa tumor, controlled all the major confounders (namely radiotherapy, tumor characteristics, damages to the deep cerebellar nuclei and delay between surgery and assessment time) and reported that early cerebellar damage (≤ 7 years old) is an independent factor for poor long-term functional (cognitive and motor) outcome [ 6 ].This suggests that the cerebellum is a sort of “broad learning machine”, and that during critical periods of development, the cerebellum, as part of a distributed neural network, is the foundation for future motor and cognitive learning.…”
Section: The Ees Cerebellum In Childrenmentioning
confidence: 99%
“…Clinical studies reporting the outcome of patients with acute cerebellar injury or chronic neurodegeneration have shown that the degree of cognitive impairment and the long-term effect of the injury is worse in younger children [ 1 , 6 ]. Preterm cerebellar injuries are also associated with poor motor and cognitive outcome [ 59 ].…”
Section: The Shifting Cerebellar Role In Ees Processing From Childhoo...mentioning
confidence: 99%
“…Although symptomatic posterior fossa tumors are typically resected, it has been reported that posterior fossa surgery may have a critical impact on the sensorimotor and cognitive outcomes of children. 14,15 The current management of brain tumors in children is evolving due to an improved understanding of the molecular mechanisms, even though biomarkers are lacking. The complementary information provided by PET and MRI, for example, SUV and ADC, could improve tumor characterization and, indirectly, the use of molecular targeted therapies.…”
mentioning
confidence: 99%